KRITIK HUKUM ISLAM TERHADAP PENDAPAT IMAM AL-SYÂFI‘Î DAN IBNU HAZM TENTANG NAFKAH BAGI ISTRI NUSYUZ - Ummi Mar’atus Sholihah (Asy-Syari'ah, 2014)
Nafkah is one of the important things in the household. Therefore, the rules relating to nafkah is needed to be studied. However, there is a different opinion among the jurists on the issue of the nafkah, such as a matter of nafkah for wives who nushuz. Imams Al-Syâfi‘î, one of the leading jurists and one of the imams mazhab argued that a wife who nushuz could abort a right to get nafkah, unless she returned from her nushuz (disobedience). This perspective is different with the opinion of Ibn Hazm which he stated that providing nafkah for wife who nushuz is allowed. He was due to differences methodology and basic laws that are based on the determining of the jurisdictions and laws through both their opinion about nafkah for nushuz’s wife.